Totally laparoscopic total gastrectomy with Uncut Roux-en-Y for gastric cancer may improve prognosis: A propensity score matching comparative study - Chen, Yizhen; Zheng, Tao; Chen, Yifan; Zheng, Yuanyuan; Tan, Song; Liu, Shaolin; Zhou, Yuhang; Lin, Xiaojun; Chen, Weijie; Mi, Yulong; Lin, Shentao; Yang, Changshun; et al. (Frontiers in Oncology, 2022)
Background: Laparoscopic total gastrectomy (LTG) with Roux-en-Y (RY) is often accompanied by Roux stasis syndrome (RSS). Uncut RY (URY) can effectively reduce RSS in laparoscopic distal gastrectomy. To determine whether totally LTG (TLTG) with URY for gastric cancer (GC) can replace RY in short-term and long-term prognosis. Methods: This comparative retrospective study selected GC patients from 2016 to 2022. The patients were divided into URY group and RY group. Cox multivariate proportional hazard regression analysis was used to explore the independent prognostic factors. Propensity score matching (PSM) was used to reduce bias. Results: A total of 100 GC patients met the inclusion criteria. Compared to RY group, URY group showed significant advantages in operation time and length of hospital stay. In addition, URY group can significantly reduce short-term and long-term complications, especially RSS. The 1-, 3- and 5-year PFS of URY group and RY group were 90.4% vs. 67.8% (P=0.005), 76.6% vs. 52.6% (P=0.009) and 76.6% vs. 32.8% (P<0.001), respectively. After PSM, the advantage of URY in PFS was verified again, while there was no significant difference in overall survival (OS) between the two groups. Cox multivariate analysis suggested that lower RSS was associated with better PFS. Conclusions: TLTG with URY for GC helps control disease progression, speed up recovery and reduce short and long-term complications, especially RSS.